Penelopa w poezji nowogreckiej XX wieku (Penelope in Modern Greek 20th century Poetry) - Bzinkowski, Michał (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2016)
In my paper I focus on the well-known Greek mythical as well as literary figure, known mainly from Homer’s Odyssey, Odysseus’ faithful wife, Penelope. Attention is given to the interpretation of the Homeric prototype in Modern Greek 20th century poetry. The successive metamorphoses of the image of Penelope are traced in Nikos Kazantzakis’ The Odyssey, Yiannis Ritsos’ Penelope’s Despair, Katerina Anghelaki-Rooke’s Says Penelope, Kyriakos Charalambides’ Penelope Recognizes Odysseus, Penelope’s Odysseusand Pandelis Boukalas’ Penelope. The analysis shows ambiguous attitude to the traditional image of Penelope and tendency of Modern Greek poets to demythologize her and to show the scene of anagnorisis in Homer‘s Odyssey in modern context as well as with more psychological probability.